The Effectiveness of Experimental Method in Teaching Motion Topic at Senior High School Level - Riskawati R; Dewi Hikmah Marisda (Universitas Muhammadiyah Makassar, 2020)
Experimentation is one of the learning process activities that is very instrumental in increasing the success of the teaching and learning process, especially in science subjects. Learning methods with practicum can be used as alternative learning that can encourage students to learn independently and actively so that they can reconstruct their learning outcomes. This study aims to determine the effect of the experimental method on student physics learning outcomes. The type of research used is true experimental research with posttest only control design. The population in this study were students of X-MIA 9 grade at SMA Negeri 9 Makassar. Samples were taken by cluster random sampling technique, obtained X-MIA 9 as the experimental class 1 and X-MIA 6 as the control class, with each consisting of 28 students. Learning outcomes obtained by students 'physics show a comparison of the scores of students' physics learning outcomes taught by using the dominant experimental method in the medium category while the results of the physics learning outcomes for students taught by using the discussion method as conventional learning dominant are in the low category. Based on the results of the study it can be concluded that learning by using the experimental method can affect students' physics learning outcomes..Keywords: Experimental Method, Physics Learning OutcomesEksperimen merupakan salah satu kegiatan proses pembelajaran yang sangat berperan dalam meningkatkan keberhasilan proses belajar mengajar khususnya dalam mata pelajaran sains. Metode pembelajaran dengan praktikum dapat digunakan sebagai alternatif pembelajaran yang dapat mendorong peserta didik untuk belajar mandiri dan aktif sehingga dapat merekonstruksi hasil belajarnya. Penelitian ini bertujuan untuk mengetahui pengaruh metode eksperimen terhadap hasil belajar fisika peserta didik. Jenis penelitian yang digunakan yaitu penelitian true eksperimen dengan desain posttest only control design. Populasi dalam penelitian ini adalah siswa kelas X-MIA 9 SMA Negeri 9 Makassar. Sampel diambil dengan teknik cluster random sampling, diperoleh X-MIA 9 sebagai kelas eksperimen 1 dan X-MIA 6 sebagai kelas kontrol, dengan masing-masing terdiri dari 28 peserta didik. Hasil belajar yang diperoleh fisika peserta didik memperlihatkan perbandingan skor hasil belajar fisika peserta didik yang diajar dengan menggunakan metode eksperimen dominan berada pada kategori sedang sedangkan hasil skor hasil belajar fisika peserta didik yang diajar dengan menggunakan metode diskusi sebagai pembelajaran konvensional dominan berada pada kategori rendah. Berdasarkan hasil penelitian dapat disimpulkan bahwa pembelajaran dengan menggunakan metode eksperimen dapat mempengaruhi hasil belajar fisika peserta didik.Kata kunci: Metode Eksperimen, Hasil Belajar Fisika